A LITERATURE REVIEW ON VARIOUS DIE MATERIALS AND DIE SYSTEM - Dr. Anwar Hussain; Dr. Ravi Gupta; Dr. Vasundhra; Dr. Mohit Bansal (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
For the fabrication of the successful fixed dental prosthesis, accurate duplication of the tooth that is prepared in the mouth is very much essential. The final clinical success of the fixed dental prosthesis, depends upon the accuracy of the impression, durability of the die. Most of the clinicians faced problems with fit of long span fixed dental prosthesis. Clinicians usually faced problems in relation to sectioning of long span fixed dental prosthesis. These steps also increased in chair time of the dentist as well as the patient, increase the cost of the procedure. To reduce the number of the clinical steps, accuracy of the working cast should be enhanced, by choosing a impression material with good reproduction details, improving the accuracy of the die system also results in accurate fit of the fixed dental prosthesis. A cast die system helps in capturing the necessary information, which can be transported to the laboratory 1-3